2013
DOI: 10.1021/la304664x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Dilational Rheology of Mixed β-Casein/DoTAB Layers Formed by Sequential and Simultaneous Adsorption at the Water/Hexane Interface

Abstract: The interfacial behavior of β-casein (βCS) has been investigated in presence of the cationic surfactant dodecyl trimethyl ammonium bromide (DoTAB) at the water/hexane interface and compared to that obtained for the water/air interface. The used experimental technique is a drop profile analysis tensiometer specially equipped with a coaxial double capillary, which allows investigation of sequential adsorption of individual components besides the traditional simultaneous adsorption of two species. This method als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…The elasticity modulus shows a pseudo-plateau for the lowest surfactant concentration, dropping with the increase of the surfactant concentration to a nearly zero value in the proximity of the CTAB cmc. The latter dependence is similar to that found by Dan et al for the rheological response of ␤-casein and dodecyl trimethyl ammonium bromide [38]. It is noticeable that the mod(E) values in the two cases are about overlapping at large concentration, which confirms the same feature observed for the -c isotherms.…”
Section: Effect Of Surfactant On the Sw Interfacial Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…The elasticity modulus shows a pseudo-plateau for the lowest surfactant concentration, dropping with the increase of the surfactant concentration to a nearly zero value in the proximity of the CTAB cmc. The latter dependence is similar to that found by Dan et al for the rheological response of ␤-casein and dodecyl trimethyl ammonium bromide [38]. It is noticeable that the mod(E) values in the two cases are about overlapping at large concentration, which confirms the same feature observed for the -c isotherms.…”
Section: Effect Of Surfactant On the Sw Interfacial Propertiessupporting
confidence: 89%
“…In fact, the plateau in the low-concentration range is similar to those found in other systems where similar effects are speculated, such as polyelectrolytes with opposite charged surfactants [33][34][35][36] or proteins with surfactants [37] and in particular what observed [38] for a similar cationic surfactants (DTAB) interacting with proteins (␤-casein).…”
Section: Effect Of Surfactant On the Sw Interfacial Propertiessupporting
confidence: 86%
“…At a fixed pH the surfactant charge significantly influences the conformation and hydrophobic/hydrophilic balance of the formed protein/surfactant complexes [40,41,43], i.e. their surface activity, and subsequently the adsorption, desorption and rheological characteristics of the mixed adsorption layer [15,19,20,28,32]. At pH 7 the SDS/BLG complexes are in an intensive competition for the surface area with increasing amount of unbound surfactant molecules [26,27,36].…”
Section: Discussionmentioning
confidence: 99%
“…Schematics of the experimental protocols used in this study are shown in Fig. A1 in the supplementary data [15,19,20]. Briefly, they consist of several stages, namely simultaneous adsorption (Sim): (I) adsorption from mixed protein/surfactant solution; and (II) washing out with pure buffer; sequential adsorption (Seq): (I) adsorption from protein solution; (II) washing out with pure buffer; (III) drop volume exchange with surfactant solution; and (IV) washing out with pure buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation